Farm Laws - Kumar, Abhishek (Trinity Law Review, 2021)
In June 2020, the Central Government presented three ordinances focusing on extensive  agricultural changes in the nation. Government has expressed that the objectives of the Act are  to Freeing up controls on trade, changing administrative framework, giving hindrance free  trade and establishing a farmer-friendly environment. These ordinances will override all State  laws in this regard. But this was all done in absence of a strong opposition and without  consulting with the states, farmers and the commission agents, who are the main affected  parties, resulting in a strong opposition and demand for rollback of the ordinances.
Keywords: framework; strong opposition; Farm Laws